Membangun Mental Positif Buruh Perempuan Korban PHK Pandemi Covid 19 di Kawasan Industri Pulogadung, Jakarta Timur - Melda Rumia Rosmery Simorangkir; Hendrikus Male; Mesta Limbong; Anne Grice Issabella (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Various levels of society experience the condition of the COVID-19 pandemic; its influence is enormous in multiple sectors. Meanwhile, during the pandemic period, a quarantine is imposed to break the chain of COVID-19. The entire community must carry out work, worship, and study activities from home. During the quarantine process, they are confused about what to do, so they often conflict with themselves and with people outside themselves. So that a positive mentality must be built to be able to motivate yourself. The method used in this community service is individual counseling; counseling is carried out on female workers who are victims of layoffs in the Pulogadung industrial area, East Jakarta. Through community service activities, female workers who are victims of layoffs learn how to motivate themselves by seeing their potential and the good side of every incident. The workers also help each other and direct others to always think positively and be ready to rise to face the pandemic conditions with a healthy mentality.